The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/0103-8478cr20200616
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation and co-encapsulation of bioactive compounds for application in food: challenges and perspectives

Abstract: The availability of different food products containing bioactive compounds promotes their inclusion in the daily diet of consumers. However, the effective and safe delivery of such products requires certain precautions to ensure their preservation, stability, and bioavailability when consumed. Microencapsulation is a great alternative, which is a method capable of protecting different bioactive compounds, including probiotic cells, prebiotic compounds, and some antioxidant substances such as phenolic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…However, encapsulated bacteria may suffer from stress due to environmental changes, resulting in reduced metabolism. Thus, the combination of two or more wall materials (bioactive compounds) in a single matrix was able to improve the viability and efficiency of co‐encapsulated cells compared with that of the encapsulated cells (da Conceição et al., 2021; Eratte et al., 2018; Raddatz & de Menezes, 2021; Vaziri et al., 2018). These results are identical to those obtained by Eratte et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, encapsulated bacteria may suffer from stress due to environmental changes, resulting in reduced metabolism. Thus, the combination of two or more wall materials (bioactive compounds) in a single matrix was able to improve the viability and efficiency of co‐encapsulated cells compared with that of the encapsulated cells (da Conceição et al., 2021; Eratte et al., 2018; Raddatz & de Menezes, 2021; Vaziri et al., 2018). These results are identical to those obtained by Eratte et al.…”
Section: Resultsmentioning
confidence: 99%
“…Encapsulation of bioactive compounds or whole cells for oral administration has been achieved with the aid of several materials, including collagen, gelatin, alginate, chitosan, gum Arabic, maltodextrin, starch, sodium caseinate, polyvinyl alcohol, polyethylene glycol, and polyacrylic acid [15][16][17][18][19]. Polymeric materials, particularly hydrogels, have been described as the preferred choice due to characteristics such as hydrophilic porous matrix, flexibility, high biocompatibility and biodegradability, prolonged consistency, userfriendliness, low cost, and ease of access [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Rashidinejad et al (2022) assure that probiotic/prebiotic co-encapsulation is an effective method of administration of probiotic live cells and that a greater survival efficiency of probiotics can be achieved during the encapsulation process and the manufacture and storage of food. Likewise, Raddatz & Menezes (2021) and Youssef et al (2021) reported different studies with an increase in the survival of probiotic cells by co-encapsulating.…”
Section: Co-encaspulationmentioning
confidence: 99%